Microbiological Profile of Corneal Ulcer in Dr. Mohammad Hoesin General Hospital Palembang, Indonesia: July to September 2021 - Rezandi Aziztama; Anang Tribowo (Sriwijaya Journal of Ophthalmology, 2022)
Introduction: Microbial agents cause infectious processes, which may result in corneal inflammation leading to corneal necrosis, ulceration, and perforation. This disorder is one of the major etiologies of monocular blindness in developing countries in Asia, Africa, and the Middle East. The etiology of corneal ulcers varies in different regions. Methods: This research is a descriptive study approach. Data obtained from the medical records of patients who were registered as corneal ulcer patients in Dr. Mohammad Hoesin Palembang from July 2021 to September 2021. Results: A total of 9 patients were diagnosed with a corneal ulcer. The number of corneal ulcer patients was more in male patients (77.8%). The age of patients varies from 16 years to 63 years, and most elderly patients are diagnosed with this condition. Predisposing factors are unknown in most patients. The most common location for ulcers is the central cornea (88.9%), with >6 mm in size. Hypopyon is found in 2 patients (22.2%), while perforation and corneal melting in 1 patient consecutively. The most common microbiological profiles of corneal ulcer patients in this study are unspecified (66.7%), while ulcers due to bacteria in the second place of the microbiological profile (33.3%) consist of Enterobacter aerogenes, Staphylococcus epidermidis, and Pantoea spp and sensitive to almost all kinds of antibiotics. Conclusion: The most common microbiological profiles of corneal ulcer patients in this study are unspecified, while ulcer due to bacteria in the second place of the microbiological profile consists of Enterobacter aerogenes, Staphylococcus epidermidis, and Pantoea spp and sensitive to almost all kinds of antibiotics.